2021
DOI: 10.1016/j.jtho.2021.01.1622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Follow-Up Surveillance After Curative-Intent Treatment of NSCLC on Detection of New and Recurrent Disease, Retreatment, and Survival: A Systematic Review and Meta-Analysis

Abstract: Introduction: Patients with NSCLC may be treated with curative intent, yet they remain at high risk of both disease recurrence and second primary lung cancer (SPLC) and increased risk of early death. Guidelines provide recommendations for follow-up, but there is little consensus, and review of available evidence is necessary. The use of a systematic follow-up strategy for the detection of disease recurrence or SPLC after curative-intent treatment of NSCLC may increase the proportion of patients available for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Consequently, guidelines recommend close surveillance after therapy to detect recurrence. Nonetheless, the optimal frequency and type of imaging are still contentious subjects due to a lack of high-quality prospective studies [3].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, guidelines recommend close surveillance after therapy to detect recurrence. Nonetheless, the optimal frequency and type of imaging are still contentious subjects due to a lack of high-quality prospective studies [3].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of studies demonstrated the diagnostic usefulness of PET/CT in patients with suspected NSCLC recurrence [9,10]. However, the utility of FDG PET/CT surveillance in detecting recurrent lesions in NSCLC patients without any clinical symptoms or other abnormal imaging findings has not been established [11]. While some previous studies reported an excellent diagnostic performance of 96-97% for FDG PET/CT surveillance [12,13], others failed to demonstrate its improved diagnostic efficacy compared to conventional imaging [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This long‐term follow‐up mandate has contributed to an institutional burden. There are limited time and resources being allocated to assess patient vital status 10 years postdiagnosis, as clinical researchers shift away from a survival framework to a curative or recurrence framework 6–8 in this timeframe. Quantified estimates of CTR burden demonstrate that 12.4 full‐time equivalents are needed to accommodate the current work conducted at an average registry, with an estimate 20% of a single registrar's work week being spent on active and passive follow‐up 9,10 …”
Section: Introductionmentioning
confidence: 99%